2022
DOI: 10.1186/s12913-022-07546-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on diagnostic pathology in the Netherlands

Abstract: Background The COVID-19 pandemic has a huge impact on healthcare provided. The nationwide pathology registry of the Netherlands, PALGA, offers an outstanding opportunity to measure this impact for diseases in which pathology examinations are involved. Methods Pathology specimen numbers in 2020 were compared with specimen numbers in 2019 for 5 periods of 4 weeks, representing two lockdowns and the periods in between, taking into account localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…As also observed in other studies investigating the number of new diagnoses of solid tumors, in our study, we observed a decrease in new diagnoses during the first trimester of the pandemic, with a recovery in the following months ( 12 , 14 21 ). We also analyzed the type of the first visit made and we noticed a reduction in the number of all types of accesses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As also observed in other studies investigating the number of new diagnoses of solid tumors, in our study, we observed a decrease in new diagnoses during the first trimester of the pandemic, with a recovery in the following months ( 12 , 14 21 ). We also analyzed the type of the first visit made and we noticed a reduction in the number of all types of accesses.…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted by Ferrara and colleagues in Central and Northern Italy, a 44.9% reduction in new cancer diagnoses in 2020 was registered, with skin melanoma being the most affected tumor with a 56.7% reduction, followed by colorectal cancer (46.6%), prostate cancer (45%), and bladder cancer (43.6%) ( 13 ). Several studies have shown similar data, with a reduction in new cancer diagnoses in spring 2020 and a recovery to 2019 numbers in the second half of the year ( 14 21 ). In literature, different studies analyzed whether there was a diagnostic delay due to the COVID-19 pandemic in different cancer types, showing in most cases that a high standard of care had been maintained during the COVID-19 peak of the pandemic, with for example no delay between diagnosis and treatment in head and neck cancers and no diagnostic or treatment onset delay in lung cancers ( 12 , 22 ).…”
Section: Introductionmentioning
confidence: 56%
“…These factors resulted in reductions in cancer presentation via all avenues, especially in primary care and outpatient departments [2] , [3] . These processes were affected by decisions made early in the pandemic to prioritise essential health services in primary and secondary care to manage COVID -19 patients and impose strict infection control measures in the UK and across Europe [4] , [5] , [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has widely affected cancer care delivery in these countries. Substantial declines in the number of cancer diagnoses have been reported in the Netherlands [4][5][6], Spain [7], Belgium [8], and Denmark [9]. While trying to minimize the risk of COVID-19 disease in cancer patients, changes in practice were pursued by oncologists, according to each setting's capacity and recommendations released by oncology societies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%